FLCN Regulates HIF2α Nuclear Import and Proliferation of Clear Cell Renal Cell Carcinoma - Xuyang Zhao; Xuyang Zhao; Yadong Ma; Jie Cui; Haiyang Zhao; Lei Liu; Yueyuan Wang; Pengxiang Min; Lin Zhang; Yongchang Chen; Jun Du; Jun Du; et al. (Frontiers in Molecular Biosciences, 2020)
Aims and Hypothesis: This study aims to explore the specific molecular mechanism of folliculin (FLCN)-induced proliferation, migration, and invasion in clear cell renal cell carcinoma (ccRCC) and to investigate the relationship of FLCN and HIF2α. Folliculin was identified as a tumor suppressor gene. Its deletions and mutations are associated with a potential risk of renal cancer. At present, the specific molecular mechanism of FLCN-induced proliferation, invasion, and migration in ccRCC remains elusive.Methods: Cell proliferation was measured by flow cytometry analysis, while cell migration and invasion were measured by wound healing assay and Matrigel invasion assay. The expression of FLCN, HIF2α, MMP9, and p-AKT was examined by Western blotting. The cells were transfected with plasmids or siRNA to upregulate or downregulate the expression of FLCN. Immunofluorescence microscopy was carried out to display the HIF2α location. We also determined the correlation of FLCN and HIF2α in human renal cancer samples.Results: FLCN was combined with HIF2α in renal tubular epithelial and cancer cells, and it effectively alleviates the deterioration of renal cancer cells by degrading HIF2α. The silencing of FLCN showed a promotion of HIF2α protein expression via PI3K/mTORC2 pathway, which in turn led to an increase in downstream target genes Cyclin D1 and MMP9. Moreover, interfering with siFLCN advanced the time of HIF2α entry into the nucleus.Conclusions: Our study illustrated that FLCN could be a new therapeutic target in ccRCC. FLCN combined with HIF2α and identified a novel PI3K/mTORC2/HIF2α signaling in ccRCC cells.